CULTIVATING READING-LOVING CHARACTER THROUGH PICTURE STORYBOOK-BASED LITERACY PRACTICES IN EARLY CHILDHOOD EDUCATION - Sunarsih, Sunarsih; Hasanah, Hisbiyatul; Priatiningsih , Selasi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of picture storybook media in fostering a reading-loving character among early childhood learners at KB Raudlatul Ulum Ledokombo Jember. Previous studies have predominantly emphasized early literacy skills, language development, and reading interest, while limited attention has been devoted to examining picture storybooks as a medium for character formation, particularly within Islamic early childhood education settings in rural areas. This study contributes to the conceptual understanding that reading-loving character is developed through the integration of literacy habituation, enjoyable reading experiences, and supportive literacy environments. The findings reveal that children voluntarily visit reading corners, actively engage in storytelling activities, and demonstrate sustained enthusiasm for reading through repeated exposure to picture storybooks. This study employed a qualitative approach using a descriptive case study design. The research was conducted at KB Raudlatul Ulum Ledokombo Jember involving eight informants, consisting of one principal, two teachers, two parents, and three children who actively participated in literacy activities. Data were collected through classroom observations, semi-structured interviews, and documentation, while data analysis involved data reduction, organization, interpretation, and conclusion drawing to identify recurring themes related to reading character formation. The findings indicate that picture storybooks function not only as instructional media but also as an effective means of cultivating reading-loving character. Literacy facilities, teacher motivation, and parental involvement emerged as supporting factors, whereas limited home literacy resources and excessive digital media exposure became major challenges. Nevertheless, picture storybooks consistently maintained children's reading enthusiasm and promoted sustainable literacy habits from an early age.